Tensões e desafios na construção de espaços e encontros entre feministas jovens autonomistas no contexto brasileiro e latinoamericano (2011-2014) - Laura França Martello (2015)
The practices and proposals of young feminisms are diverse and have gained more expression in the feminist field. Through fieldwork and interviews with participants, the research mapped young feminist practices, focusing autonomist feminist gatherings and festivals that happened in Brasil, including a Latin Americanencounter, from 2011 to 2014. Situating these expressions in its continuities and ruptures with other feminist activisms through the movement's historical trajectory, and reviewing the debates and conflicts that have taken place in Latin-American gatherings in the last decades political context, we analyzed how the young autonomist feminist seek social transformation through the formation of resistance communities and cultures which offer the support to enable the living relations shaped by feminist principles in the present within quotidian bases. These activisms are characterized by the creation of methodologies and pedagogies for the formation of self-consciousness and self-determination through the sharing of subjective experiences, interpretative framings for the reality, techniques of self-defense and other bodily micropolitics. The analyses of the field focused on organizational practices of the movements, presenting and reflecting critically, along with the discourses of the research collaborators on proposals of: autonomy, self-management and do-it-yourself, the creation of spaces for women, lesbians and trans, the creation of mutual care and support, and the search for horizontality. The research also analyzed conflicts over power relations and the forms of fighting oppression within feminists, specially ageism and adultocentrism, lesbophobia, transphobia, racism, and specism.